Frontispiece: Asymmetric Catalytic (2+1) Cycloaddition of Thioketones to Synthesize Tetrasubstituted Thiiranes. Issue 19 (24th April 2022) - Lin, Xiaobin; Pu, Maoping; Sang, Xinpeng; Li, Shiyang; Liu, Xiaohua; Wu, Yun‐Dong; Feng, Xiaoming
Abstract : Asymmetric Catalysis Tetrasubstituted thiiranes can be synthesized by an asymmetric catalytic (2+1) cycloaddition of thioketones as reported by Xiaohua Liu, Yun‐Dong Wu, Xiaoming Feng et al. in their Research Article (e202201151) .